Mapping waste generation and economic growth: Insights from input-output analysis in Malta (Global Journal of Human-Social Science, 2024)
The search for an economy that is not riddled with externalities is an ongoing one However to reach this objective policy making must shift its focus from the end of pipe solutions and obtain a deeper understanding of the connection that economic development and growth holds with environmental degradation This study focuses on the connection that the economy holds with waste generation and via the application of the Waste Input Output model it puts forward estimatesillustrating how a 1-million injection in final demand impacts total waste generation considering both direct and indirect production and waste generation effects The research is based on the Maltese Islands and uses 2015 as a base year This is in view that the most recent inputoutput tables published by the national statistics office are built on this year Results note that the waste generated by the construction industry remains by far the largest with 1 535 07 tonnes generated for every 1 million Other concerning figures arise from the health and social work and agricultural sectors which result in 523 33 and 135 57 tonnes of waste respectively when there is an injection of 1 million euros The magnitude of this figure is often watered down due to the inert properties of the waste generated however the disposal of construction and demolition can cause various difficulties particularly on islands where the problem of space is ubiquitous
Keywords: waste input output analysis; waste multipliers; direct and indirect waste generation; economic growth; waste treatment